Comparison of the Effectiveness of U-Shape Toothbrushes and Conventional Toothbrushes for Cleaning Dental Plaque: A Narrative Review - Pindobilowo; Grace Monica; Dwi Ariani (Jurnal Multidisiplin Madani, 2023)
Introduction: Tooth brushing is an act of dental and oral health care that is most performed by the community. The function of brushing teeth is to control plaque so as not to cause dental and oral diseases, namely caries and gingivitis. People often do practical things, namely by using an electric toothbrush, where the toothbrush is not yet known how effective it is in removing dental plaque. Purpose: to find out the differences in the effectiveness of U-Shape electric toothbrushes and conventional toothbrushes in cleaning dental plaque. Methods: This literature study uses the narrative review method. Journals and references were collected through the BMC Oral Health, PubMed and Google Scholar online databases and websites which were selected selectively and in accordance with this literature study. Conclusion: The use of a U-Shaped toothbrush shows results that are not effective in removing plaque and is equivalent to not brushing your teeth at all and brushing your teeth using a conventional toothbrush is also still better at removing plaque